Bất định ESG, nắm giữ tiền mặt, và ổn định tài chính của các công ty trên thị trường chứng khoán Việt Nam - Nguyễn Hữu , Mạnh; Nguyễn Thành , Cường; Vương Thị Hương, Giang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of Environmental, Social, and Governance (ESG) uncertainty on corporate cash holding decisions and financial stability among Vietnamese firms over the period 2010–2024. Using panel data of companies on the HOSE, HNX, and UPCOM exchanges in Vietnam and applying various panel econometric techniques, the study finds that higher ESG uncertainty increases cash holdings while reducing financial stability, supporting the precautionary motive under heightened uncertainty. The results also indicate that the effects of ESG uncertainty are heterogeneous across the three stock exchanges. For firms in the neutral sector, ESG uncertainty negatively affects cash-holding decisions, as ESG-related shocks do not significantly influence their financial stability. Overall, the study provides novel empirical evidence on the role of ESG uncertainty in shaping corporate financial decisions in an emerging market.